Implementing a return-to-work strategy in the Belgian Disability Benefits Insurance Scheme. (12th November 2014) - Perl, François
Abstract : Background : Belgium has more than 300.000 disabled people excluding work injuries or professional diseases. Until 2009, there was no return to work or disability management programs in the Belgian disability benefits public insurance. Objectives : Facing a huge increase of disability pension claims since 2007, the Belgian Government charged the NIHDI (public social security agency) to implement a national "return to work" program. This program aims to offer options and stimulate part time job recovery or vocational training initiatives. Methods : Since Belgium is a Federal State, the need for cooperation between NIHDI and the regional public employment services (PES) was essential. NIHDI implemented various contracts with the PES and with the Mutual Benefits Societies (semi private bodies in charge of the claim processing and the medical assessment). These contracts include objectives, financing and evaluation criteria. The NIHDI uses the expertise of international experts in return to work strategies and disability management. Findings : The interaction between PES and physicians from NIHDI and Mutual Benefits Societies is essential. There is a strong need for medical, disability management and social guidelines in order to prevent any risk of differential results. The traditional claim processing is outdated. It is essential to integrate from the beginning of the claim processing, strong objectives for helping the social insured to return to work as soon as possible.